Change in women's status in modern China: New challenges and opportunities - L.S. Veselova (Ученые записки Казанского университета: Серия Гуманитарные науки)
The period of the late 20th – early 21st centuries was marked by political, economic, and social changes in China. Among these transformations, the change in the status of Chinese women stands out. The Chinese society, patriarchal in nature, has always been prejudiced against women and their social role. They were seen as domestic goddess destined to continue the family line. However, the period of reform and opening up that began in the 1980s, as well as the single child policy, changed the familiar way of life in China: women in China began to take more leadership positions, many of them are listed among the most influential people of the world. The birth of a daughter in the Chinese family used to be perceived as a tragedy. However, everything has changed: daughters became worthy successors of the family business and manage it successfully and profitably. At the same time, the change in the women’s status brings a number of issues and problems into the social and economic life. Chinese employers and the Chinese labor market as a whole started to face more and more problems.